PENGARUH KONVERGENSI IFRS DAN CLIENT ATTRIBUTES TERHADAP PENETAPAN BIAYA AUDIT EKSTERNAL - Novriany Suhantinar, Tiara; Juliarto, Agung (Diponegoro Journal of Accounting, 2014)
This research aims to test the influence of IFRS convergence and client attributes on the determination of external audit fees. Client Attributes in this research consist of financial distress, type of industry and number of subsidiaries. This research is based on research conducted by Gammal (2012), Kusharyanti (2012), Suharli and Nurlaelah (2008) with modifications on the variables and sample. In addition to client attributes, this research is modified by including variables of IFRS convergence, financial distress and type of industry.The research used secondary data from the annual reports of all companies listed on the Indonesian Stock Exchange (IDX) from 2010 to 2013. Sampling method used in this study was purposive sampling. A total sample of 131 companies were used in analysis. The data is analyzed using multiple linear regression analysis.The result of this research show that IFRS convergence, type of industry and number of subsidiaries positively affect the determination of external audit fees. This study, however, does not find significant effect of financial distress on the determination of external audit fees.